Thermal process for magnesium production with Al-Si-Fe from coal fly ash: Thermodynamics and experimental investigation - Yu Q.-C.; Deng Y.; Yin S.-B.; Li Z.-Y. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Dumping or disposal of fly ash causes environmental pollution and huge waste of valuable metals. In this work, carbothermic reduction of fly ash under normal pressure to produce Al-Si-Fe alloy, and thermal reduction of magnesia to produce magnesium in vacuum with Al-Si-Fe alloy were investigated. In addition, the surface morphology and composition of Al-Si-Fe alloy and magnesium were studied by means of SEM-EDS and XRD. Based on the thermodynamic analysis, it was found that AlN and SiO2 lowered down the reduction temperature of SiC and Al4C3, respectively. Increase of temperature and decrease of vacuum degree promotes the thermal reduction of magnesia. Results showed that the recovery rate ranked Fe, Si, and Al in a descending order. The evaporation loss of gaseous SiO and Al2O reduced the recovery of Si and Al. Al-Si-Fe alloy containing 33.12% Al, 48.73% Si, and 6.41% Fe is obtained under the optimal conditions. Magnesium with the content of 94.87% is prepared using the obtained Al-Si-Fe alloy as a reductant. The nucleation rate is less than the growth rate during the condensation of magnesium vapor.